Predicting adult literacy and numeracy: Findings from the British cohort study - Adrian Furnham; Helen Cheng (Acta Psychologica)
This study investigates factors that predict adult literacy and numeracy using a large, stratified, and nationally representative sample of 5397 adults (48.6 % females) in the UK. Results showed that parental social status (at birth), childhood intelligence (at age 10), teenage internal locus of control (at age 16), educational qualifications and occupational levels (at ages 26 and 30) were all significantly and positively associated with adult literacy and numeracy (at age 34). Structural equation modelling showed that childhood intelligence, teenage locus of control, malaise, and education and occupation all had significant and direct effects on adult literacy and numeracy, accounting for 53 % of the total variance. The strongest predictor of adult literacy and numeracy was childhood intelligence, followed by educational qualifications and teenage locus of control. Results revealed that the effect of parental social status on adult literacy and numeracy was mediated mainly through educational qualifications. Limitation in terms of self-report biases, attrition and some cross-sectional variables is acknowledged. Implications are considered.